Pengaruh Produk, Harga, Distribusi, dan Promosi Terhadap Volume Penjualan pada PT. Sari Jaya Kharisma Abadi di Jombang - muhammad afif; Krisdianto Krisdianto (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2020)
This study aims to determine the effect of product, price, distribution, and promotion on the sales volume of PT. Sari Jaya Kharisma Abadi in Jombang. The method used is quantitative, namely by collecting, presenting and analyzing data from consumers using a questionnaire to 30 respondents. The data analysis technique in this study is multiple linear regression to determine the effect simultaneously, partially and dominantly. Based on the results of the research simultaneously the effect of product, price, distribution, and promotion on sales volume is significant (0.00). From the research results partially the effect of product is significant (0.05), significant price (0.00), significant distribution (0.02), and significant promotion (0.03) on sales volume. Among the influence of product, price, distribution, and promotion on sales volume of PT. Sari Jaya Kharisma Abadi in Jombang, the most dominant is the price which is influenced by indicators including: price and discount.